STUDI TENTANG PESERTA DIDIK YANG MEMILIKI EGO ORANG DEWASA DI KELAS X SMA KEMALA BHAYANGKARI - Willy, Thomas; Yuline, Yuline; Putri, Amallia (Universitas Tanjungpura, 2024)
This research examines the Ego Status of Adults in students. Aims to know and describe the adult ego status in class X students of SMA Kemala Bhayangkari Kab. Kuburaya. The subjects of this study consisted of 3 class X students and 7 supporting subjects: three classmates, three class teachers, and one counseling teacher. This research used a qualitative approach with descriptive methods. Data collection techniques used in-depth interviews and observation. Data analysis uses an interactive model consisting of data reduction, data display, and drawing conclusions/verification stages. This research is reviewed from the scope of transactional analysis theory. The results obtained are symptoms of adult ego in students such as being independent, having a patient nature, thinking rationally, being responsible, and being expressive. Factors causing adult ego are physical conditions, parental teaching/parenting, living environment, and school. The impact of the adult ego is on decision-making, rigid actions, being an audience in difficult times, and dominating in groups and learning. BK teachers try to approach students who have an adult ego. It can be seen that adult ego can be in the form of feelings, actions, and behaviors arising from learners.